2021
DOI: 10.1002/lary.29424
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of Pharmacologic Treatments for COVID‐19: Safety Considerations and Ototoxicity

Abstract: Objective/Hypothesis The purpose of this review is to summarize evidence‐based data regarding the ototoxic effects of potential COVID‐19 therapeutics to treat patients suffering from SARS‐CoV‐2. Methods Medications under investigation as novel therapeutics to treat COVID‐19 were identified using the search term coronavirus therapeutics , COVID therapeutics , and SARS‐CoV‐2 therapeutics on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 72 publications
(77 reference statements)
0
30
0
1
Order By: Relevance
“…33 Another antiviral agent, ribavirin, is known to cause severe SNHL if prescribed alongside interferon, even if the data about ototoxic effects of ribavirin alone are scarce. 34 Specific references on the history of exposure to ototoxic drugs were reported in 4 over 20 patients and these cases are included in this review. 7,10,14,24 All patients received hydroxychloroquine alone or in association to other established potential ototoxic drugs, such as azithromycin or furosemide; a clear correlation between their symptoms and the adverse effects of these medications was not established.…”
Section: Ototoxicity Of Covid-19 Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Another antiviral agent, ribavirin, is known to cause severe SNHL if prescribed alongside interferon, even if the data about ototoxic effects of ribavirin alone are scarce. 34 Specific references on the history of exposure to ototoxic drugs were reported in 4 over 20 patients and these cases are included in this review. 7,10,14,24 All patients received hydroxychloroquine alone or in association to other established potential ototoxic drugs, such as azithromycin or furosemide; a clear correlation between their symptoms and the adverse effects of these medications was not established.…”
Section: Ototoxicity Of Covid-19 Treatmentsmentioning
confidence: 99%
“…Another antiviral agent, ribavirin, is known to cause severe SNHL if prescribed alongside interferon, even if the data about ototoxic effects of ribavirin alone are scarce. 34 …”
Section: Ototoxicity Of Covid-19 Treatmentsmentioning
confidence: 99%
“…
In Reply:We would like to thank Narozny et al for their interest in our publication "A narrative review of pharmacologic treatments for COVID-19: safety considerations and ototoxicity" and their insightful comments regarding the association between severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and sudden sensorineural hearing loss (SSNHL). 1,2 We agree with the authors that any COVID-19 patients experiencing SSNHL should be considered high-risk and receive urgent audiologic evaluation.The growing body of literature regarding the incidence of SSNHL in COVID-19 patients, whether it be through exposure to ototoxic agents or due to SARS-CoV-2 infection itself, highlights the importance for all members of a patient's care team to maintain vigilance regarding the symptoms of SSNHL. Quick recognition and diagnosis of SSNHL, regardless of exposure to ototoxic agents, may be critical to recovery of audiologic function, audio-vestibular sequelae and improve quality of life.
…”
mentioning
confidence: 60%
“…We would like to thank Narozny et al for their interest in our publication "A narrative review of pharmacologic treatments for COVID-19: safety considerations and ototoxicity" and their insightful comments regarding the association between severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and sudden sensorineural hearing loss (SSNHL). 1,2 We agree with the authors that any COVID-19 patients experiencing SSNHL should be considered high-risk and receive urgent audiologic evaluation.…”
mentioning
confidence: 60%
“…
We read with colossal interest the manuscript of Little et al entitled "A narrative review of pharmacologic treatments for COVID-19: safety considerations and ototoxicity." 1 The authors concluded that among those infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), high-risk patient groups treated with ototoxic drugs should be given special attention, such as the elderly and hearing impaired. We agree with the authors of the publication.
…”
mentioning
confidence: 99%